2022
DOI: 10.1155/2022/6149369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Survival Risk and Immune-Related Characteristics of Kidney Renal Clear Cell Carcinoma

Abstract: Background. Immunity exerts momentous functions in the progression and treatment of kidney renal clear cell carcinoma (KIRC). A better understanding of the relationship between KIRC and immunity may make a great contribution to evaluating the prognosis and immune-related therapeutic response of KIRC. Methods. A series of information such as RNA sequence, clinical data, and tumor mutation burden (TMB) of KIRC patients were downloaded through The Cancer Genome Atlas (TCGA). Next, combining the survival informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Theoretically, the number of neoantigens that can be recognized by T cells increases with TMB, and immunotherapy improves. However, T cells may be in a dysfunctional state, and the prognoses of patients with high TMB are poor, consistent with the previous study of ccRCC (68,69). Tumor immune escape can better predict the prognosis of patients than TMB and PD-L1, and T cell dysfunction is an important cause of immune escape (70).…”
Section: Discussionsupporting
confidence: 87%
“…Theoretically, the number of neoantigens that can be recognized by T cells increases with TMB, and immunotherapy improves. However, T cells may be in a dysfunctional state, and the prognoses of patients with high TMB are poor, consistent with the previous study of ccRCC (68,69). Tumor immune escape can better predict the prognosis of patients than TMB and PD-L1, and T cell dysfunction is an important cause of immune escape (70).…”
Section: Discussionsupporting
confidence: 87%
“…Immune infiltration, immune regulators and TIME were evaluated to study the differences in immune microenvironment characteristics among these distinct apoptosis modification patterns. ImmuneScore, StromalScore, ESTIMATEScore, and TumorPurity were obtained from ESTIMATE algorithms [ 21 ], and ImmuneScore, StromalScore, and ESTIMATEScore were the lowest in C2, while TumorPurity Score was the highest in C2 (Fig. 8 C).…”
Section: Resultsmentioning
confidence: 99%
“…However, in cancers where CD8 + T cells were not correlated with neoantigen load (prostate, breast, glioma, etc), the ORR was lower in both TMB‐H and TMB‐L patients. In renal clear cell carcinoma, TMB‐H patients had even lower response rates to ICIs than TMB‐L patients 24 . In addition, Xiaofeng Chen et al 23,25 found that TMB‐H in patients with advanced BTC was associated with poor prognosis and poor immunotherapy effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In renal clear cell carcinoma, TMB-H patients had even lower response rates to ICIs than TMB-L patients. 24 In addition, Xiaofeng Chen et al 23,25 found that TMB-H in patients with advanced BTC was associated with poor prognosis and poor immunotherapy effectiveness. Thus, whether TMB-H can be used as a biomarker to predict the therapeutic effect of ICIs in patents with BTC requires further in-depth investigation.…”
Section: Treatment-related Adverse Events (Traes)mentioning
confidence: 99%